Pleomorphic adenoma of retrobulbar ectopic lacrimal gland: a rare occurrence - Dr. Jadhav Dnyaneshwar S.; Dr. Pawar Prajakta S.; Dr. Gadkari Rasika U.; Dr. Giri Apoorv (Tropical Journal of Pathology and Microbiology, 2017)
Ectopic lacrimal gland encompasses all lacrimal tissue that is outside the lacrimal gland fossa, excluding the accessory glands of Krause and of Wolfring. The bulbar conjunctiva and limbus are most commonly involved regions while retrobulbar region is unusual. This tissue may undergo neoplastic transformation, the commonest tumour being pleomorphic adenoma. A 30 year old male presented with painless loss of vision and mild proptosis of the right eye since 5 months. MRI disclosed a well-defined, lobulated contrast enhancing mass in the right retrobulbar region measuring 2 X 2 X 2 cm and a differential diagnosis of vascular or glial neoplasm was entertained. Excision biopsy revealed an encapsulated mass away from the lacrimal fossa. Histopathology showed features of pleomorphic adenoma which was confirmed on IHC.